The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s10915-020-01202-3
|View full text |Cite
|
Sign up to set email alerts
|

A Fully Discrete Mixed Finite Element Method for the Stochastic Cahn–Hilliard Equation with Gradient-Type Multiplicative Noise

Abstract: This paper is concerned with fully discrete mixed finite element approximations of the time-dependent stochastic Stokes equations with multiplicative noise. A prototypical method, which comprises of the Euler-Maruyama scheme for time discretization and the Taylor-Hood mixed element for spatial discretization is studied in detail. Strong convergence with rates is established not only for the velocity approximation but also for the pressure approximation (in a time-averaged fashion). A stochastic inf-sup conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Recent PDE studies in this direction can be found in [364,142,396,442,441], those stochastic PDEs involve gradient-type multiplicative noise and thus have stronger nonlinearity. Finite element approximations have been carried out in [198] for a stochastic Allen-Cahn equation with gradient-type multiplicative noise and in [200] for a related stochastic Cahn-Hilliard equation with gradient-type multiplicative noise. Not surprisingly, their sharp interface models are expected to be a stochastic mean curvature flow [364] and a stochastic Hele-Shaw model [200,19], respectively.…”
Section: Fluid and Solid Mechanicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent PDE studies in this direction can be found in [364,142,396,442,441], those stochastic PDEs involve gradient-type multiplicative noise and thus have stronger nonlinearity. Finite element approximations have been carried out in [198] for a stochastic Allen-Cahn equation with gradient-type multiplicative noise and in [200] for a related stochastic Cahn-Hilliard equation with gradient-type multiplicative noise. Not surprisingly, their sharp interface models are expected to be a stochastic mean curvature flow [364] and a stochastic Hele-Shaw model [200,19], respectively.…”
Section: Fluid and Solid Mechanicsmentioning
confidence: 99%
“…Finite element approximations have been carried out in [198] for a stochastic Allen-Cahn equation with gradient-type multiplicative noise and in [200] for a related stochastic Cahn-Hilliard equation with gradient-type multiplicative noise. Not surprisingly, their sharp interface models are expected to be a stochastic mean curvature flow [364] and a stochastic Hele-Shaw model [200,19], respectively. However, their rigorous convergence proofs are still missing although some partial results were reported in [364,19] and positive numerical results were given in [196,198,200].…”
Section: Fluid and Solid Mechanicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The paper [15] presented the analysis of strong convergence rate of an implicit full discretization applied to stochastic Cahn-Hilliard equation with unbounded noise diffusiton in dimension one. The authors of [23] derived strong convergence rates of a fully discrete mixed FEM for the stochastic Cahn-Hilliard equation with gradient-type multiplicative noise, where the noise process is a real-valued Wiener process.…”
Section: Introductionmentioning
confidence: 99%
“…The stochastic wave equations with Lipschitz continuous nonlinear drift term and diffusion term were studied using the semi-group approach in [2,17,19,43]. As a comparison, the multiplicative noise is considered in this paper based on the variational approach (see [27,28,29,30]), and the nonlinear drift term is not Lipschitz continuous.…”
mentioning
confidence: 99%